Analysis of Semarang City Government's Mitigation Efforts to Reduce Flood Disaster Risk to Support National Security - Onggo Cahyo Wibowo; Ernalem Bangun; Bambang Wahyudi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Disasters are closely linked to human security, which of course is also closely linked to national security. Se Bang Fai is known as a flood-prone district. This study aims to analyze the flood control efforts carried out by the Semarang city government. Disaster is a serious threat to the social life of the existing society and finally to the stability of the nation. The threat that the citizens of Indonesia feel is the frequency of disasters that occur in almost all of Indonesia. Semarang, which is the capital of Central Java province, is vulnerable to flooding. Floods in Sepon City started to occur frequently between 2017 and 2021. Disaster reduction is one of the efforts of the Sepon City Government to reduce the risk of flood disasters. One of the mitigation efforts implemented by the Semarang city government is the construction of the West Tidal Canal and the East Tidal Canal. The construction of 2 rivers: the East Canal and the West Canal is expected to reduce the flood disaster in Sam Nua District. The government must prepare a flood preparedness plan so that the government knows what to do to reduce future flood disasters.